2020
DOI: 10.3390/ijfs8030051
|View full text |Cite
|
Sign up to set email alerts
|

Financial Risk and Financial Performance: Evidence and Insights from Commercial and Services Listed Companies in Nairobi Securities Exchange, Kenya

Abstract: In Kenya, the last few years has seen the performance of companies listed under the commercial and services segment on the Nairobi Securities Exchange (NSE), experience mixed fortunes. The study sought to assess the implications of financial risk on the performance of these companies. The study applied explanatory research design. The target population were the 14 companies listed under this segment of NSE. Secondary panel data contained in published annual reports for the period 2013–2017 was collected. Panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 20 publications
4
15
1
Order By: Relevance
“…This means that the higher the credit risk led the higher the Financial Distress. The results of this study have also shown a consistent with the research of Brownbridge (1998), Rahman et al (2004), Fukuda et al (2007, Zaki et al (2011), Kargi (2011), Keffala (2018, Gadzo et al (2019), Onsongo et al (2020), Ledhem and Mekidiche (2020), Asutay and Othman (2020), Kablay and Gumbo (2020). Results also found a positive effect of Credit risk on Financial Distress, so the hypothesis statement in thi study is accepted.…”
Section: Hypothesis Testingsupporting
confidence: 91%
See 1 more Smart Citation
“…This means that the higher the credit risk led the higher the Financial Distress. The results of this study have also shown a consistent with the research of Brownbridge (1998), Rahman et al (2004), Fukuda et al (2007, Zaki et al (2011), Kargi (2011), Keffala (2018, Gadzo et al (2019), Onsongo et al (2020), Ledhem and Mekidiche (2020), Asutay and Othman (2020), Kablay and Gumbo (2020). Results also found a positive effect of Credit risk on Financial Distress, so the hypothesis statement in thi study is accepted.…”
Section: Hypothesis Testingsupporting
confidence: 91%
“…Banks in financial stress condition and even on verge of bankruptcy will disrupt payment system activities and will disrupt the distribution of credit loans to local communities (Gilbert and Meyer, 1991). Researchers who still pay attention to financial stress, including Keffala (2018), Gadzo et al (2019), Ledhem and Mekidiche (2020), Onsongo et al (2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…According to research conducted by Widajatun & Ichsani (2019) OEIR has a negative and significant effect on ROA. In contrast to research conducted by Onsongo et al, (2020) where the results of OEIR have a positive effect on ROA.…”
Section: Introductioncontrasting
confidence: 85%
“…This means that a decrease in foreign exchange risk results to increase in financial performance of listed investment firms. In agreement, a study by Onsongo, Muathe, and Mwangi (2020) found a negative significant relationship between foreign exchange risks and financial performance (ROA and ROE). However, the results contradict a study by Panda and Leepsa (2017) that found that foreign exchange risk had positive significant relationship with financial performance.…”
Section: Regression Analysissupporting
confidence: 65%
“…However, the study used GLS which is difficult to interpret. In another study, Onsongo, Muathe, and Mwangi (2020) assessed the implications of financial risk on the performance of commercial and services companies. The study collected secondary data for the period 2013-2017.…”
Section: Financial Risks and Financial Performancementioning
confidence: 99%